Impact of active tuberculosis on social mobility and its gender differences: Difference in differences using nationwide tuberculosis surveillance data and national health insurance data - Daseul Moon; Dawoon Jeong; Young Ae Kang; Gyeong In Lee; Hongjo Choi (PLoS ONE, 2025)
Although reducing catastrophic total costs caused by TB is a major public health concern, there is a scarcity of long-term follow-up studies on social suffering due to TB as well as studies examining gender gaps. This study aims to examine the degree of long-term change in household incomes due to active TB by gender. We created data for the TB and control groups by linking the Korean National Tuberculosis Surveillance System (KNTSS) and National Health Information Database (NHID) and covariate-adjusted propensity score matching (PSM). We created longitudinal panel data from two years before TB diagnosis (t) to two years after TB diagnosis and analyzed the changes in household income deciles by gender and group using a difference in differences (DID) model. In men, there was a clear trend of declining income since time t in the TB group (DID coefficient = −0.131 95% CI = −0.132 ~ −0.129), but there was no marked change in women. Subgroup analyses on the working-age population (20–65 years) (DID coefficient = −0.053, 95% CI = −0.096 ~ −0.010) and employee population (DID coefficient = −0.072, 95% CI = −0.110 ~ −0.034) showed a trend of declining income in the female TB group. This study showed that there is a marked trend of declining income due to the diagnosis and treatment of active TB in men but not in women. This discrepancy may be attributable to the differences in gender roles in a patriarchal society and higher possibility of women moving out of the labor market after disease. There is a pressing need for comprehensive and universal implementation of health and social protection policies to alleviate the trend of social suffering caused by disease.